ESR/ERS statement paper on lung cancer screening. Issue 2 (13th February 2020) - Kauczor, Hans-Ulrich; Baird, Anne-Marie; Blum, Torsten Gerriet; Bonomo, Lorenzo; Bostantzoglou, Clementine; Burghuber, Otto; Čepická, Blanka; Comanescu, Alina; Couraud, Sébastien; Devaraj, Anand; Jespersen, Vagn; Morozov, Sergey; et al.
In Europe, lung cancer ranks third among the most common cancers, remaining the biggest killer. Since the publication of the first European Society of Radiology and European Respiratory Society joint white paper on lung cancer screening (LCS) in 2015, many new findings have been published and discussions have increased considerably. Thus, this updated expert opinion represents a narrative, non-systematic review of the evidence from LCS trials and description of the current practice of LCS as well as aspects that have not received adequate attention until now. Reaching out to the potential participants (persons at high risk), optimal communication and shared decision-making will be key starting points. Furthermore, standards for infrastructure, pathways and quality assurance are pivotal, including promoting tobacco cessation, benefits and harms, overdiagnosis, quality, minimum radiation exposure, definition of management of positive screen results and incidental findings linked to respective actions as well as cost-effectiveness. This requires a multidisciplinary team with experts from pulmonology and radiology as well as thoracic oncologists, thoracic surgeons, pathologists, family doctors, patient representatives and others. The ESR and ERS agree that Europe's health systems need to adapt to allow citizens to benefit from organised pathways, rather than unsupervised initiatives, to allow early diagnosis of lung cancer and reduce the mortality rate. Now is the time to set up and conduct demonstration programmes focusing, among other points, on methodology, standardisation, tobacco cessation, education on healthy lifestyle, cost-effectiveness and a central registry. The ESR and ERS agree that Europe's healthcare systems need to allow citizens to benefit from organised pathways to early diagnosis and reduction of mortality of lung cancer. Now is the time to set up and implement large-scale programmes. http://bit.ly/2miF0cO